2013
DOI: 10.5941/myco.2013.41.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Color of Light Emitting Diode on Development of Fruit Body in Hypsizygus marmoreus

Abstract: This study was conducted to identify a suitable color of light for development of the fruit body in Hypsizygus marmoreus. To accomplish this, samples were irradiated with blue (475 nm), green (525 nm), yellow (590 nm), or red (660 nm) light emitting diodes (LEDs) to induce the formation of fruiting bodies after mycelia growth. The diameter and thickness of the pileus and length of stipes in samples subjected to blue LED treatment were similar to those of subjected to fluorescent light (control), and the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 8 publications
2
38
0
1
Order By: Relevance
“…Soil casing is an important step to stimulate fruiting in the cultivation process of A. bisporus and Volvaria volvacea [19]. The casing soil can maintain the temperature, humidity, and CO 2 necessary for primordium differentiation [2], and more importantly, some bene cial microorganisms (Bacillus, Arthrobacter, Pseudomonas putida) present in this soil have a signi cant effect on the growth and morphogenesis of the edible fungi [22,23]. Therefore, these bene cial microorganisms are naturally present in the production of edible mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Soil casing is an important step to stimulate fruiting in the cultivation process of A. bisporus and Volvaria volvacea [19]. The casing soil can maintain the temperature, humidity, and CO 2 necessary for primordium differentiation [2], and more importantly, some bene cial microorganisms (Bacillus, Arthrobacter, Pseudomonas putida) present in this soil have a signi cant effect on the growth and morphogenesis of the edible fungi [22,23]. Therefore, these bene cial microorganisms are naturally present in the production of edible mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in accord with those seen in Coprinopsis cinerea (Terashima et al 2005) and Hy. marmoreus (Namba et al 2002;Jang et al 2013). The breadth of the pilei of the fruiting bodies grown under NUV light was twice that of those grown under blue light (Fig.…”
Section: Primer Name Sequencementioning
confidence: 95%
“…In Hebeloma vinosophyllum, blue and NUV light are the most effective wavelengths for induction of primordia (Kitamoto 1977). In Hypsizygus marmoreus (buna-shimeji), blue light is effective in producing high-quality fruiting bodies (Namba et al 2002;Jang et al 2013). In Lentinula edodes (shiitake), blue light photoreceptors PHRA and PHRB, homologs of Neurospora crassa white collar (WC)-1 and WC-2, respectively, have been identified (Sano et al 2007;Sano et al 2009), andTang et al (2013) reported that these blue light photoreceptors are associated with light-induced brown film formation.…”
Section: Introductionmentioning
confidence: 96%
“…Light: The fruiting bodies of most Agaricomycetes, including Lentinula edodes (shiitake, oak mushroom) and Pleurotus ostreatus (oyster mushroom), require light to develop properly (Jang et al, 2013). Fruiting-body formation of Coprinus cinereus is perfectly synchronized to the light-dark rhythm fixed by the normal day-night cycle.…”
Section: Cultivation Conditionsmentioning
confidence: 99%
“…To initiate the fruiting body development, several environmental signals are needed, of which dark and light periods are the most important (Kües, 2000). Jang et al (2013) studied the effect of color of light emitting diode (LED) on development of fruiting body of Hypsizygus marmoreus (shimeji) and found out that the cultivation under blue LED (475 nm) resulted in the formation of fruiting bodies with good features, e.g. high ergosterol level.…”
Section: Cultivation Conditionsmentioning
confidence: 99%